ASSESSING PRE-UNIVERSITY STUDENTS’ VISUAL REASONING: A GRAPHICAL APPROACH - Hamid, Haliza Abd; Idris, Noraini (Asian Journal of Assessment in Teaching and Learning, 2014)
The importance of understanding graph in the learning of calculus had led to calls for an increased i visual reasoning skills among secondary through university levels. The effectiveness of graphs in understanding derivatives depends on their efficacy as visual text forms aimed to illustrate and communicate two or more related information. Providing students with an approach to reading and interpreting graphs will help them to understand concepts better. Therefore, the study focussed on how to assess 194 pre-university students’ ability to read and interpret graphical form of functions and their derivatives based on the decoding theory: reading the graph, reading between the graph and reading beyond the graph. Findings indicate that students were able to read information directly but faced difficulties when reading beyond the graph. Implications and future research directions are discussed.